Evaluation of gastric emptying in critically ill patients using electrical impedance method: a pilot study. (4th July 2022) - Basher, Ariful; Moniruzzaman, Mohammad; Islam, Md. Maruful; Rashid, Md. Mahbubur; Chowdhury, Iqbal Hossain; AKM, Akhtaruzzaman; Rabbani, Khondkar Siddique-e
Abstract: Nasogastric feeding is commonly used to deliver enteral feed in critically ill patients and several methods are used for assessing the gastric residual volume with limitations. A new approach for gastric emptying time measurement has been developed using Electric Impedance Method (EIM). The study aims to establish whether EIM is useful for measuring gastric emptying during nasogastric feeding compared with nasogastric suction. The pilot study was performed among the patients in the Intensive Care Unit (ICU), Bangladesh, from 2018 to 2019. Enteral feed was given to patients by NG tube. Gastric emptying and Gastric Residual Volume (GRV) were measured using EIM and nasogastric suction tube. Patterns of filling and emptying were almost the same in all subjects but emptying time varied between individuals that correlated well with GRV in 16 patients. Therefore, the study showed that the measurement of gastrc volume by the non-invasive and hazard-free electrical impedance method has a high specificity (90%) and efficacy of 80%. The study also revealed significant changes in gastric emptying time due to different body statuses. EIM seemed to be capable of measuring gastric emptying over time. EIM could become a standard tool for monitoring gastric emptying in patients at risk of gastroparesis.